What is Core to A Brand? An Examination of The Brand Elements and Their Subsequent Impact on the Consumer - Mahajan, Nikhil (2006)
Abstract: The number of brands is proliferating. Approximately 3000 brands are introduced each year into supermarkets. There were at the time of writing 750 nameplates of cars, over 150 brands of lipstick, and 93 cat-food brands(Aaker, 1991, p. 8). Fifteen years down the line, undoubtedly this number has increased substantially. The propagation of media and distribution channels, have provided a thrust to the view that the brand and what it represents is the most important asset for many companies and is the basis for competitive advantage and profits (Keller, 2003). In support, Davis (2000) and Sheppard (1994) share a common view that brands are among a company's most powerful assets. From these opinions, it is clear to see the importance and benefits of owning a strong and memorable brand and this seems to be the core agenda of all major companies. It is believed by the researcher that academics, managers and other professionals would all benefit from understanding what elements are at the heart of a successful brand and as such, this document aims to provide a thorough understanding of the diverse elements of branding and investigate the importance of each element in the consumers mind. The researcher tries to accomplish his set objectives by using the primary research method of focus groups. The results from this research indicate that there are three core elements out of the various elements put under the scanner, which provided a basis for recommendations for further research.